Exploration of the Central Figures Character of the Ramayana Story in Balinese Prasi: Overview Based on Iconographic Aspects - I Wayan Suardana (Budapest International Research and Critics University, 2022)
Exploration of the characters of the Ramayana characters, where the search for the characters of this writing aims to: examine the iconographic aspects of the characters of the key figures of the Ramayana stories, understand the form of the aesthetic expression of the art of Prasi Ramayana. The character iconography of the Ramayana character, Prasi art is in accordance with the classical wayang style of Kamasan style with decorative forms in which Rama, Shinta, Ravana, Hanuman, and Jatayu birds are factually the central figures. These figures play an important role in the Ramayana story. The shapes of animals, buildings, rocks and mountains are made closer to realists using perspective. The existence of the Prasi Ramayana art has the support of the Balinese people, general art activities, especially the Prasi art are closely related to Hindu religious ceremonies and activities with the character of the figures in the context of art and religion in society because they are interrelated.